La Aguada pottery in the highlands (Puna Meridional Argentina, Catamarca) - Casanova, Martín Tomás; Olivera, Daniel Enzo; Pérez, Martina Inés (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2020)
This paper presents a technological and decorative study of a ceramic sample identified with the Aguada typology from the Casa Chávez Montículos site in Antofagasta de la Sierra, (Puna Meridional Argentina). The characteristics of this pottery, result of the proposed analysis, will be compared with similar attributes of the pieces coming from the mesothermal valleys of Hualfín and Abaucán analyzed by other authors. The objective of the comparison is to identify similarities and differences in the different steps of the production process of this type of pottery. Thus, new data will be contributed to the discussion, raised (Olivera, 1992; 1997), about the region from which the influence that led to the Aguada presence in Antofagasta de la Sierra during the Middle and Late Formative period (2000 to 1100 BP) came, while analyzing the particular characteristics of Aguada in Antofagasta de la Sierra.